Refugees, Islamophobia, and Ayaan Hirsi Ali: Challenging Social Work Co-Option - Briskman, Linda; Latham, Susanna (2017)
© 2016, © The Author(s) 2016. As global discourses on refugees and Muslims become more exclusionary, the ethics and traditions of our profession mean social workers arguably have a particular responsibility to work for transformative change. This column argues that social workers need to be wary of direct complicity with harsh policies through implementation roles and, indirectly, through co-option into dominant discourses about refugees and Islam more generally and Muslim women specifically.